Thermo‐triggered Release of CRISPR‐Cas9 System by Lipid‐Encapsulated Gold Nanoparticles for Tumor Therapy. (15th January 2018) - Wang, Peng; Zhang, Lingmin; Zheng, Wenfu; Cong, Liman; Guo, Zhaorong; Xie, Yangzhouyun; Wang, Le; Tang, Rongbing; Feng, Qiang; Hamada, Yoh; Gonda, Kohsuke; Hu, Zhijian; et al.
Abstract: CRISPR/Cas9 system is a powerful toolbox for gene editing. However, the low delivery efficiency is still a big hurdle impeding its applications. Herein, we report a strategy to deliver Cas9‐sgPlk‐1 plasmids (CP) by a multifunctional vehicle for tumor therapy. We condensed CPs on TAT peptide‐modified Au nanoparticles (AuNPs/CP, ACP) via electrostatic interactions, and coated lipids (DOTAP, DOPE, cholesterol, PEG2000‐DSPE) on the ACP to form lipid‐encapsulated, AuNPs‐condensed CP (LACP). LACP can enter tumor cells and release CP into the cytosol by laser‐triggered thermo‐effects of the AuNPs; the CP can enter nuclei by TAT guidance, enabling effective knock‐outs of target gene ( Plk‐1 ) of tumor (melanoma) and inhibition of the tumor both in vitro and in vivo. This AuNPs‐condensed, lipid‐encapsulated, and laser‐controlled delivery system provides a versatile method for high efficiency CRISPR/Cas9 delivery and targeted gene editing for treatment of a wide spectrum of diseases.